METHODS AND APPROACHES TO IMPROVING ENGLISH LANGUAGE TEACHING - Fayzullayev, Furkatjon (Журнал иностранных языков и лингвистики, 2023)
I forget. Show me, I remember. Involve me, I understand. There are many methods of teaching languages. Some have had their heyday and have fallen into relative obscurity; others are widely used now; still others have a small following, but contribute insights that may be absorbed into the generally accepted mix. English Language Teaching is now at a crucial juncture as a number of methods, approaches and innovations have been discussed. There are four skills of language learning Listening, Reading, Writing and Speaking and to fulfill these skills one has to take constant efforts until the goal is achieved. These present paper is aimed at developing teaching skills.